FEATURES OF THE INCREASED CONCENTRATION OF CARBON DIOXIDE IN THE ROOM ON THE HEALTH AND PERFORMANCE OF STUDENTS - Mirsagatova M.R, Imamova A.O., Oblokulov A. G., Muxammadzokirov S.S, Musalova L. (American Journals, 2023)
After the implementation of the "Flower Island" project in the academic year in which I took part, more indoor plants appeared in school classrooms. We decided to find out if this benefited students and teachers who spend a lot of time in these classrooms, this was the subject of the research work "The effect of indoor plants on the concentration of carbon dioxide in the premises." We came across many articles on the impact of carbon dioxide on human health and performance. We became very interested in this issue also because it is a logical continuation of my previous works.
Keywords: carbon dioxide, oxygen, pollutants, light, human health, plants, breath